Financial Technology and Behavioral Financial Management - Vera, Nevia Prima; Asria, Maya (Pascasarjana STIE Amkop Makassar, 2025)
This study examines the influence of financial technology payment usage on students’ financial management behavior. Fintech, as a technological innovation in the financial sector, offers ease, speed, and accessibility for various financial transactions. With the increasing use of digital wallets and mobile banking applications among Indonesian students, this research investigates whether such usage translates into improved financial management. Data were collected from 30 students at the Faculty of Economics and Business, Universitas Negeri Padang, who had taken finance-related courses. A simple linear regression analysis revealed a strong and statistically significant positive relationship between fintech payment usage and financial management behavior. The findings indicate that students who actively use fintech services tend to manage their finances more effectively—tracking expenses, budgeting, and making informed financial decisions. However, the study also acknowledges the need for financial literacy to prevent impulsive spending and ensure safe usage of digital financial tools. These results highlight the role of financial technology not only in facilitating transactions but also in shaping responsible financial habits among young users. Further research is recommended to explore additional factors influencing financial behavior beyond fintech usage.